1995
DOI: 10.1152/jappl.1995.79.2.581
|View full text |Cite
|
Sign up to set email alerts
|

Surges of muscle sympathetic nerve activity during obstructive apnea are linked to hypoxemia

Abstract: Obstructive sleep apnea (OSA) is associated with oscillations of arterial blood pressure (BP) that occur in phase with irregularities of respiration. To explore the role of the sympathetic nervous system in these responses, we studied muscle sympathetic nerve activity (MSNA; peroneal microneurography), an index of vasoconstrictor nerve traffic, and BP during awake regular breathing and during spontaneous apneas in patients with OSA. To determine the role of the arterial chemoreflex, we also examined the effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
193
2
2

Year Published

1999
1999
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 242 publications
(205 citation statements)
references
References 0 publications
8
193
2
2
Order By: Relevance
“…[5] It is likely that the same mechanisms are valid in humans too, since obstructive sleep apnea leads to increased SNS activity and increased daytime blood pressure. [6][7][8] Obstructive breathing disorders are associated with cardiovascular diseases such as hypertension, [9][10][11] myocardial infarction, [12] stroke, [13] and heart failure. [14] When treated with continuous positive airway pressure (CPAP) during sleep, daytime blood pressure and sympathetic activity decrease.…”
Section: Introductionmentioning
confidence: 99%
“…[5] It is likely that the same mechanisms are valid in humans too, since obstructive sleep apnea leads to increased SNS activity and increased daytime blood pressure. [6][7][8] Obstructive breathing disorders are associated with cardiovascular diseases such as hypertension, [9][10][11] myocardial infarction, [12] stroke, [13] and heart failure. [14] When treated with continuous positive airway pressure (CPAP) during sleep, daytime blood pressure and sympathetic activity decrease.…”
Section: Introductionmentioning
confidence: 99%
“…Reflex effects leading to changes in autonomic tone may be activated through 1) changes in thoracic mechanics from obstructed respiratory efforts (4), 2) changes in blood-gas tensions (hypoxia and/or hypercapnia) (12,18), and 3) postapneic arousals. These factors ultimately culminate in an increase in sympathoadrenal tone (9,13), which is associated with a pressor response during the apnea and postapnea periods. Studies to date have focused mainly on the relative effect of these physiological alterations with regard to the overall cardiovascular response to apneas.…”
mentioning
confidence: 99%
“…Our data demonstrate that the pressor response to apneas in this model is dependent to a large extent on the vagus nerve. Sympathetic activation during periodic apneas is thought to occur from reflex effects elicited from hypoxia, possibly hypercapnia and mechanical alterations (6,9,12,13,18). These physiological alterations cause activation of peripheral and central sensors, including baroreceptors, chemoreceptors, and mechanoreceptors.…”
mentioning
confidence: 99%
“…[10][11][12] SDB was related with heart strain due to apnea and various cardiovascular diseases. Some studies have reported a relationship between SDB and myocardial ischemia, 2,[13][14][15] arrhythmia, [16][17][18] sudden death, 19) platelet coagulation, 20) and inflammatory cytokines, 21,22) all of which may trigger heart failure.…”
Section: Discussionmentioning
confidence: 99%